Cooperative group learning: the use of brainstorming to promote speaking skills among form four students / Polin Bearing - Bearing, Polin (2015)
The use of a variety of brainstorming activities has great potential to promote speaking skills in English as a Second Language (ESL) classroom. This exploratory research sets out to explore the types of brainstorming activities used to promote students' speaking skills and to find out how brainstorming activities in cooperative group learning can promote speaking skills. Students' and teachers' perspectives on the use of brainstorming in cooperative group learning are gathered to seek the opinions on how brainstorming helps to promote students' speaking skills. In this study, 321 Form Four students of an urban secondary school in Kuching were involved. The data were obtained through the analysis of students' questionnaire, interviews with three language teachers as well as the observations in classes during the cooperative group learning sessions. From the findings, it was found that the types of brainstorming activities most frequently used by English teachers to promote speaking skills are using word lists, word mapping and pictures. The study also indicated that both students and teachers have positive perceptions towards the use of brainstorming activities in cooperative group learning to promote speaking skills. The study concludes by providing some recommendations that this strategy has pedagogical implications that are relevant to students and teachers as it contributes to the increase in students' motivation, confidence and participation as shown from students' positive behaviour during classroom observations. Hence, findings from this study provide a new insight and knowledge in understanding how the use of brainstorming in cooperative group learning can promote speaking skills to reduce anxiety and reluctance of students speaking in the second language.